Regional Variation in Nonoperative Therapy Utilization for Symptomatic Lumbar Stenosis and Spondylolisthesis: A 2-Year Costs Analysis. Issue 2 (April 2020) - Davison, Mark A.; Lilly, Daniel T.; Moreno, Jessica; Cheng, Joseph; Bagley, Carlos; Adogwa, Owoicho
Study Design: Retrospective cohort study. Objectives: To characterize regional variations in maximal nonoperative therapy (MNT) costs in patients suffering from lumbar stenosis or spondylolisthesis. Methods: Medical records from patients with symptomatic lumbar stenosis or spondylolisthesis undergoing primary ≤3-level lumbar decompression and fusion procedures from 2007 to 2016 were gathered from a large insurance database. Geographic regions (Midwest, Northeast, South, and West) reflected the US Census Bureau definitions. Records were searchable by International Classification of Diseases diagnosis/procedure codes, Current Procedural Terminology codes, and insurance-specific generic drug codes. Utilization of MNT, defined as cost billed, prescriptions written, and number of units disbursed, within 2-years prior to index surgery was assessed. Results: A total of 27 877 patients underwent 1-, 2-, or 3-level lumbar decompression and fusion surgery. Regional breakdown of the study cohort was as follows: South 62.3%, Midwest 25.2%, West 10.4%, Northeast 2.1%. Regional variations in the number of patients using nonsteroidal anti-inflammatory drugs (NSAIDs) ( P < .0001), opioids ( P < .0001), muscle relaxants ( P < .0001), and lumbar steroid injections ( P < .0001) were detected. A significant difference was identified in the regional MNT failure rates ( P < .0001). The total cost associated with MNT prior to index surgery was 48 411 125 (1736.60/patient), with the Midwest (1943.83/patient) responsible for the greatest average spending. Despite comprising 62.3% of the cohort, the South was accountable for 67.5% of NSAID prescriptions, 64.6% of opioid prescriptions, and 71.2% of muscle relaxant prescriptions. Conclusions: Regional differences exist in the costs of MNT in patients with lumbar stenosis and spondylolisthesis prior to surgery. Future studies should focus on identifying patients likely to fail prolonged nonoperative management.